The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1124/jpet.117.246991
|View full text |Cite
|
Sign up to set email alerts
|

Total RNA Sequencing of Rett Syndrome Autopsy Samples Identifies the M4 Muscarinic Receptor as a Novel Therapeutic Target

Abstract: Mutations in the gene are responsible for the neurodevelopmental disorder Rett syndrome (RTT). MeCP2 is a DNA-binding protein whose abundance and ability to complex with histone deacetylase 3 is linked to the regulation of chromatin structure. Consequently, loss-of-function mutations in MeCP2 are predicted to have broad effects on gene expression. However, to date, studies in mouse models of RTT have identified a limited number of gene or pathway-level disruptions, and even fewer genes have been identified tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 57 publications
6
43
1
Order By: Relevance
“… (B) RT-PCR on RNA isolated from Rett brain versus age-matched control brains for P53 targets. (C) A re-analysis of data published by Gogliotti et al. (2018) .…”
Section: Resultsmentioning
confidence: 99%
“… (B) RT-PCR on RNA isolated from Rett brain versus age-matched control brains for P53 targets. (C) A re-analysis of data published by Gogliotti et al. (2018) .…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in KCC2 protein expression has been detected in MECP2-deficient human RTT neurons and in the brains of Mecp2 mutant mouse model of RTT (27,28), in autopsy brain samples (48), and in the cerebrospinal fluid of patients with RTT (49). To assess whether the KEECs identified above would enhance KCC2 expression in RTT neurons, we screened MECP2-null RTT human KCC2 reporter neurons (isogenic to the WT reporter cells used in Fig.…”
Section: Keecs Enhance Kcc2 Expression In Human Rtt Neuronsmentioning
confidence: 99%
“…Studies in autopsy samples have demonstrated that the expression of ~2000 genes is compromised by pathogenic mutations in MeCP2 , most of which are only moderately shifted up or down [12]. This increase in transcriptional noise is postulated to result in a series of interactomes of affected proteins that may additively contribute to the manifestation of RTT phenotypes [12]. De novo discovery efforts for RTT seek to identify nodes on these interactomes, which can serve as potentially druggable access points to modify specific symptom domains.…”
Section: Discovery Effortsmentioning
confidence: 99%
“…For example, both glutamatergic and GABAergic signaling are compromised in MeCP2 -knockout mice. Based on our experience with modulating synaptic plasticity using allosteric modulators of metabotropic glutamate (mGlu) and muscarinic receptors, we profiled human RTT and control tissues for expression of these targets and found significant changes in two metabotropic glutamate (mGlu) receptors, mGlu 5 [13] and mGlu 7 [14], as well as in the M 4 muscarinic receptor [12]. Using positive allosteric modulators that were originally under development for other indications, such as schizophrenia, we have built preclinical datasets for these novel targets in RTT model mice.…”
Section: Discovery Effortsmentioning
confidence: 99%
See 1 more Smart Citation